Implementation of solar thermal technology - Larson, Ronal W.; West, Ronald E. (Ronald Emmett), 1933-; IEEE Xplore (Online Service); MIT Press (Cambridge, Massachusetts : MIT Press, 1996)
Implementation of Solar Thermal Technology describes thesuccesses and failures of the commercialization efforts of the U.S.solar thermal energy program, from the oil embargo of 1973 throughthe demise of the program in the early Reagan administration andits afterlife since then. The emphasis throughout is on lessonslearned from the solar experience, with an eye toward applicationsto other projects as well as toward possible renewal of efforts atcommercialization.Part I discusses the history of government involvement in solardevelopment and the parallel development of the market for solarproducts. Part II looks at the histories of specific commercializationprograms for five areas (active heating and cooling, passivetechnologies, passive commercial building activities, industrialprocess heat, and high-temperature technologies). Parts III-VIIIfocus in turn on demonstration and construction projects, qualityassurance, information dissemination programs, efforts to transfertechnology to industry, incentive programs (tax credits, financing,and grants), and organizational support.Solar Heat Technologies: Fundamentals and Applications, Volume 10.
Includes bibliographical references and indexes.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/23/2015.
Keywords: Solar energy; Solar heating; Electronic books